Effects of the video assistant referee on games in the Bundesliga - Tom Böttger; Lars Vischer (Universität Münster, Institut für Organisationsökonomik, 2024)
Referees and their assistants are faced with the challenge of making correct decisions in complex and high-speed game situations. Subconscious bias on the part of referees and the resulting systematic favouring of teams have already been shown many times in sports economics and impair fairness in football. Since the 2017/2018 season, the video assistant referee (VAR) has been used as a technical support for referees to correct clearly incorrect decisions. Based on 2,448 games and 1,880 match situations reviewed by the VAR from the 2019/2020 to 2022/2023 seasons, this study examines whether the VAR is a suitable instrument to counteract the bias of referees on the field. The analyses carried out reveal that the VAR is only able to accomplish this to a limited extent. Even with technical support, human bias remains in the decision-making process. – – Schiedsrichter und ihre Assistenten stehen vor der Herausforderung, in komplexen und in hoher Geschwindigkeit stattfindenden Spielsituationen korrekte Entscheidungen zu treffen. Unterbewusste Voreingenommenheit von Schiedsrichtern und die daraus resultierende systematische Bevorzugung von Teams wurden in der Sportökonomik bereits vielfach nachgewiesen und beeinträchtigen die Fairness im Fußball. Seit der Saison 2017/2018 wird der Videoschiedsrichter (VAR) als technische Unterstützung für Schiedsrichter genutzt, um klare Fehlentscheidungen zu korrigieren. Anhand von 2.448 Partien und 1.880 vom VAR überprüften Spielsituationen der Spielzeiten 2019/2020 bis 2022/2023 wird untersucht, ob der VAR ein geeignetes Instrument ist, um dem Bias von Schiedsrichtern entgegenzuwirken. Die durchgeführten Analysen offenbaren, dass der VAR hierzu nur begrenzt in der Lage ist, denn auch mit technischer Unterstützung verbleibt menschlicher Bias im Entscheidungsprozess.
Keywords: D83; D91; L83; Z20; Z21; 650; Bias; Decision; Football; Rule; VAR